Students` Formation Of Social Competence In Foreign Language Classes (Journal of Pedagogical Inventions and Practices, 2024)
The article shows the place of social competence in the system of key competencies when applying the competency-based approach in education, and also defines the means, conditions and techniques for developing social competence in foreign language lessons.